Comparative Analysis of Retinal Nerve Fiber Layer Thickness between Normal and Mild to Moderately Myopic Eyes: Doi: 10.36351/pjo.v37i4.1219 - Nasreen, Gul; Sarwar, Shaheer Suhail; Bibi, Irfana; Ashraf, Muhammad Arslan (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the difference between mean retinal nerve fiber layer (RNFL) thickness in myopic eyes (up to -6.00D) and normal eyes. Study Design: Descriptive observational study. Place and Duration of the Study: Eye department of Mayo hospital Lahore, from February 2019 to April 2019. Methods: We compared the mean RNFL between 58 myopic eyes (up to -6.00 D) and age matched 60 normal eyes. The age of the participants was between 12 to 42 years. Complete ocular examination was done and RNFL thickness was measured by using Optical coherence tomography (NIDEX RS-33.0, software-ex 1.5.2).Data was analyzed by independent sample t-test by using SPSS; with P < .05 as significant. Results: The mean difference among these groups was 5.852 µm with (SE: 1.929). Mean RNFL thickness in myopic group was (95.93 ± 10.158µm) with (SE: 1.334). The result for mean RNFL thickness in myopic eyes was distributed normally as P < .03. Mean RNFL in normal group was (101.78 ± 10.774 µm) with (SE: 1.391), and the result of mean RNFL thickness measured in normal eyes was not distributed normally as P < .20. The results showed that there is a statistically significant difference between mean RNFL thickness measured in normal versus myopic eyes as (P < .003). Conclusion: There is a significance difference between mean RNFL thickness between myopic eyes and normal eyes as measured by OCT. Careful interpretation of RNFL data in myopic eyes is recommended to avoid misdiagnosis with glaucoma. Key Words: Retinal Nerve Fiber Layer thickness, Myopia, Optical Coherence Tomography.